2011
DOI: 10.1007/s00586-011-1817-3
|View full text |Cite
|
Sign up to set email alerts
|

Effect of the cord pretension of the Dynesys dynamic stabilisation system on the biomechanics of the lumbar spine: a finite element analysis

Abstract: The Dynesys dynamics stabilisation system was developed to maintain the mobility of motion segment of the lumbar spine in order to reduce the incidence of negative effects at the adjacent segments. However, the magnitude of cord pretension may change the stiffness of the Dynesys system and result in a diverse clinical outcome, and the effects of Dynesys cord pretension remain unclear. Displacement-controlled finite element analysis was used to evaluate the biomechanical behaviour of the lumbar spine after inse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
50
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 60 publications
(54 citation statements)
references
References 26 publications
4
50
0
Order By: Relevance
“…These studies also indicate that the high stiffness of the Dynesys system itself may be a major contributing factor to disc stress. Our previous study implanted with the Dynesys system [23] demonstrated that reducing the preload on the cord can alleviate stress of the disc and improve ROM at the adjacent levels during flexion. In a subsequent study, we changed the stiffness of the spacers by altering their diameter [24], and showed that spacers with smaller diameters reduce disc stress and ROM at adjacent levels during extension.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These studies also indicate that the high stiffness of the Dynesys system itself may be a major contributing factor to disc stress. Our previous study implanted with the Dynesys system [23] demonstrated that reducing the preload on the cord can alleviate stress of the disc and improve ROM at the adjacent levels during flexion. In a subsequent study, we changed the stiffness of the spacers by altering their diameter [24], and showed that spacers with smaller diameters reduce disc stress and ROM at adjacent levels during extension.…”
Section: Discussionmentioning
confidence: 99%
“…In our previous study we examined the effect of different cord preloads on the Dynesys system [23] and revealed that high stiffness was related to high preloads of approximately 300 N on the cord. We also demonstrated that preloads as low as 100 N can reduce facet joint contact forces and disc stress at adjacent levels during flexion.…”
Section: Introductionmentioning
confidence: 99%
“…29 The use of a 300-N cord pretension causes a much higher stiffness at the implanted level than the intact lumbar spine. 20 Because the effects of spacer length and cord tension on segmental flexibility and rigidity are still debated in the literature, many surgeons adjust the pretension below 300 N depending on the patient's condition. 24,32 Other advantages of the Dynesys system are that the procedure to implant it is less invasive than PLIF and it results in earlier recovery.…”
Section: Evaluation Of Possible Advantages Of the Dynesys Systemmentioning
confidence: 99%
“…A three-dimensional nonlinear FE model of the human lumbar spine was created using the commercial software ANSYS 11.0 (ANSYS Inc., Canonsburg, PA, USA) in our previous studies [18,19]. Much of detailed description for this lumbar spine FE model had been reported [19,20].…”
Section: Validation Of the Fe Modelmentioning
confidence: 99%
“…The DY [18,24] and the KD models ( Fig. 2) were bilaterally inserted into the L3-L4 level of the model.…”
Section: Fe Model Of the Dy And Kd Systemsmentioning
confidence: 99%